Long-term results of complete clinical and pathologic regression in patients with breast cancer - S. M. Demidov; D. A. Demidov; M. A. Zafirova (ABV-press, 2016)
The article presents the results of analysis of long-term treatment outcomes of 162 patients who received neoadjuvant chemotherapy for breast cancer based on City Clinical Hospital No. 40 of Ekaterinburg. ER-negative status, triple-negative subtype of tumor and lymph node negative status were found to be significant predictive factors of complete tumor regression. In studying long-term results of the treatment it was showed that negative status of lymph nodes significantly predicts improvement in relapse-free survival, while the surgical treatment does not increase relapse-free survival time in case of complete tumor regression.